2018
DOI: 10.1002/chem.201803149
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Promoted Intermolecular Oxidative Dearomatization of β‐Naphthols with N‐Hydroxycarbamates

Abstract: An intermolecular oxidative dearomatization of β-naphthols with N-hydroxycarbamates promoted by visible light was realized by means of photogenerated β-naphthol radical cation intermediates. With a commercially available organic dye, the naphthalenones bearing a fully substituted stereogenic center were obtained with up to 92 % yield under aerobic conditions (26 examples). In addition, the rearrangement of C-O coupling products to C-N coupling compounds could be achieved merely in the presence of Cs CO . This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…Visible‐light photo‐redox catalysis has been extensively adopted in dearomatization reactions with peculiar applications in naphthyl derivatives. In this context, a very interesting visible‐light driven intermolecular oxidative dearomatization of β‐naphthols 1 , with N ‐hydroxycarbamates 72 , was reported in the presence of highly oxidizing acridium photocatalyst PC 1 (Scheme a) . Preliminary mechanistic studies revealed the selective β‐naphthol oxidation to the corresponding radical cation intermediate A1 that can be captured by the carbamate 73 via exclusive C–O bond formation reaction.…”
Section: Light‐promoted Dearomatization Of Naphtholsmentioning
confidence: 97%
“…Visible‐light photo‐redox catalysis has been extensively adopted in dearomatization reactions with peculiar applications in naphthyl derivatives. In this context, a very interesting visible‐light driven intermolecular oxidative dearomatization of β‐naphthols 1 , with N ‐hydroxycarbamates 72 , was reported in the presence of highly oxidizing acridium photocatalyst PC 1 (Scheme a) . Preliminary mechanistic studies revealed the selective β‐naphthol oxidation to the corresponding radical cation intermediate A1 that can be captured by the carbamate 73 via exclusive C–O bond formation reaction.…”
Section: Light‐promoted Dearomatization Of Naphtholsmentioning
confidence: 97%
“…Thus, the development of eco‐friendly and abundant visible light photo‐redox catalysis into dearomatization reactions may emerge as a powerful synthetic tool and demand for immediate attention. Few successful efforts which deliver exciting carbon–heteroatom bond generations are Klussmann's report on dearomative peroxidation employing tetraphenylporphin (TPP) under the white LED and upon going through literature, we were also found that there is some literature precedence on dearomative peroxidation of phenols employing oxone as a source of singlet oxygen, Fu's synthesis of spiropyrrolines in the presence of amine under visible light and oxidative dearomatization of 2‐naphthols with N ‐hydroxycarbamates by You …”
Section: Figurementioning
confidence: 99%
“…Naphthols are also viable substrates for the direct activation with photoredox catalysts. In 2018, You and co‐workers reported an intermolecular oxidative dearomatization of 2‐naphthols 14 with N ‐hydroxycarbamates (Scheme A) . The use of [Acr‐Mes]ClO 4 ( 15 ) as a photoredox catalyst under air was essential in achieving this transformation, which led to a selective photoactivation of naphthol 14 to radical cation intermediate 17 , followed by nucleophilic capture of the resulting radical cation 17 by the carbamate with exclusive C–O bond‐forming selectivity (Scheme B).…”
Section: Assisted Photoactivation Of Arenesmentioning
confidence: 99%